2002
DOI: 10.1114/1.1484218
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Varying Adhesion Levels in Chondrocytes Using the Cytodetacher

Abstract: The potential to promote cell adhesion must be evaluated in the development of tissue-engineered implants and scaffolds. One measure of cell adherence is the force necessary to detach the cell. The objective of this study was to evaluate the cytodetacher (Athanasiou, K. A., et al. Development of the cytodetachment technique to quantify cellular adhesiveness. Biomaterials 20: 2405-2415, 1999), modified to test cells grown on substrata, as a means of calculating cell adhesion forces. Live and formalin-fixed bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The absence of bond rupture was confirmed by fluorescent imaging of the focal adhesion protein vinculin, which was observed at the periphery of the cell. Previous in vitro experiments have investigated cell adhesion and detachment during shear deformation [13,41]. A computational study [17], based on the experimental findings of Huang et al [13], illustrates that a strengthening of the cell-substrate interface in tandem with cytoplasm stiffening during cell spreading results in increased cell detachment forces.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of bond rupture was confirmed by fluorescent imaging of the focal adhesion protein vinculin, which was observed at the periphery of the cell. Previous in vitro experiments have investigated cell adhesion and detachment during shear deformation [13,41]. A computational study [17], based on the experimental findings of Huang et al [13], illustrates that a strengthening of the cell-substrate interface in tandem with cytoplasm stiffening during cell spreading results in increased cell detachment forces.…”
Section: Discussionmentioning
confidence: 99%
“…The role of shear strength on cell-material adhesion has been investigated also by Yamamoto et al [93] and Athanasioiu and coworkers [94,95]. Such a method was based on the design of a cytodetachment instrument able to quantify the force required to displace and to detach cells attached to a substratum, Fig.…”
Section: Experimental Strategies For Cell-ecm Adhesion-force Measuremmentioning
confidence: 98%
“…The averages of the cell detachment shear strengths measured on murine fibroblasts after 24 h of incubation of glass by Yamamoto et al fall in the range 500 -750 kPa, and shear force in the range 350 -580 nN. Athanasiou and coworkers used the cytodetachment to measure single-cell adhesiveness and the effect of protein on cell adhesiveness [94,95]. They found that chondrocytes present an adhesion force around 20 nN and that the fibronectin strongly increases the adhesion of the cell to the substrate, see Fig.…”
Section: Experimental Strategies For Cell-ecm Adhesion-force Measuremmentioning
confidence: 98%
“…Direct shearing of single chondrocytes was performed using a modified cytodetachment apparatus (Athanasiou et al 1999;Hoben et al 2002). This device was adapted from its original setup to allow for the videocapture of cells experiencing mechanical shear.…”
Section: Direct Shear Of Single Cells and Videocapturementioning
confidence: 99%